Relationships Among Future Skills Competency of Palliative Care Nurse and Perception of Quality in Palliative Care Services - Phutthasawat, Chatchadaporn; Apiruknapanond, Panta; Lueboonthavatchal, Oraphun (Journal of health and health management, 2025)
This descriptive research was to study the relationship between future skills and the competency of palliative nursing professionals towards perceptions of the quality of palliative care. The sample group consisted of palliative nurses who had provided care in the palliative care unit and a multidisciplinary team (nurses, doctors) that take care of palliative care patients at the government’s hospitals in Nakorn Nayok Province. The sample size calculation using G* power 3.12 program resulting in a sample size of 130. The sample was selected by simple random sampling among palliative nurses and multidisciplinary team. The research instruments consisted of two sets of instruments namely assessment form for palliative nurses and assessment form for multidisciplinary teams.Both sets of tools were divided into 4 parts 1) Personal information 2). Future skills assessment form 3). Palliative nursing assessment form.4). Assessment of perception of quality of care form which had liability values sorted by set = 0.89 and 0.90 respectively. The data were analyzed using mean ( ), Standard Deviation (SD), and Spearman’s correlation coefficient (r). The results of this research had found that the future skills of palliative nurses were at the highest level ( = 4.36, SD = 0.47), the competency of palliative nurses were at the highest level ( = 3.31, SD = 0.52), the palliative nurses’ perception of the quality of palliative care was at the highest level ( = 4.46, SD = 0.67) and the future skills of palliative nursing professionals on the perception of the quality of palliative care had a positive relationship with statistical significance at the .01 level (r = 0.77, p<.01), and the palliative nursing professional competency towards the perception of quality in palliative care has a positive relationship with statistical significance at the .01 level (r = 0.85, p<.01)